Birds mention in the Holy Qur’an and their role in the natural ecosystem - Islam, Md. Sirajul; Samsudin, Sofiah (INSI Publications, 2014)
Birds Mention in the Holy Qur‟an (BMHQ) is an important subject that plays a major role to Develop Human Thinking (DHT). Bird species have been mentioned in several verses for a different purpose and action of them; such as to develop human thinking on the sign of Allah‟s power, that how birds flying in the sky, like human and non human species birds have their own communities, bird species as communities of worshipers and valuable resource those provide aesthetic values and ecological services necessary for human well-being as well as for the natural environment. However, the main purpose of BMHQ is to prove the Sign of the Creator in Biodiversity (SCB). Therefore, the main objective of this study is to demonstrate the SCB,as well as Existence of the Creator (EC) through discussion of the Bird‟s Role in the Natural Ecosystem(BRNE) in light of the Qur‟anic philosophy and an experiment of animal scientists in order to establish the reality; that is belief in Allah SWT who is only one Creator and controller of their and the universe alike. The study has found bird species have been mentioned in the Holy Qur‟an in two methods; all bird species by use in general term, and bird use in three specific names. The bird species are: Coturnixcotumix japonica (Salwa-quail), Corvus (Gurab-crow) andUpupaepops (Hudhud-hoopoe). In fact, Allah SWT inspires to bird species the Nano Science (NS) which is a wise guided them. Consequently, all bird species are playing their role in the Natural Ecosystem (NE).To sum upthe creator Created everything for humans‟ welfare. Therefore, humans should develop their relationship with the Creator and the NE by follow Creator‟s commands and prohibitions those related tothe NE. As though human abstain themselves from abuse and torturing into bird species that cause for hazard to the NE.